Pengembangan Produk Unggulan UMKM Kabupaten Sukabumi - Kusdiana, Dikdik; Gunardi, Ardi (TRIKONOMIKA, 2014)
Micro, Small and Medium enterprises (MSMEs), in national economy, have an important and strategic role. This research examines the main product development of MSMEs in Sukabumi regency. The analysis method used is Analytic Hierarchy Process (AHP). This method is used to identify MSMEs main products in several sectors appropriate to be developed. The result shows that the potential products of MSMEs in each sector, after conducting AHP analysis based on the criteria of uniqueness, market force and economic benefits, are mangosteen, metal processing and workshop services.